Ordering History Through the Timeline - Eugenio Garibaldi; Pietro Garibaldi (Institute of Labor Economics (IZA), 2017)
History is a key subject in most educational system in Western countries, and there is ongoing concern about the the degree of historical knowledge and historical sensibility that students obtain after their high school graduation. This paper proposes a simple linetime test for quantitatively measuring a human sense of history. The paper reports the results of the test administered to approximately 250 Italian university students. There are two empirical results. First, students have remarkable difficulties in ordering basic events over the time line, with the largest mistakes observed around the events that took place in the Middle Age. Second, the paper uncovers a statistical regularity in the test performance across gender, with female subjects featuring a statistical significant and quantitatively sizable downward score. The gender difference is surprising, since existing literature on differences in cognitive abilities across gender suggests that female subjects outperform male subjects in memory related tests. The paper shows also that the gender difference survives to a variety of sub periods, and falls by only 20 percent when we distinguish between violent and non violent events.
Keywords: I12; 330; sense of time; gender differences